Traveling Wave Solutions of Nonlinear Evolution Equation via Enhanced(G/G)- Expansion Method - Islam, Md. Ekramul; Khan, Kamruzzaman; Akbar, M Ali; Islam, Rafiqul (GANIT: Journal of Bangladesh Mathematical Society, 2014)
In this article, the Enhanced (G'/G)-expansion method has been projected to find the traveling wave solutions for nonlinear evolution equations(NLEEs) via the (2+1)-dimensional Burgers equation. The efficiency of this method for finding these exact solutions has been demonstrated with the help of symbolic computation software Maple. By this method we have obtained many new types of complexiton soliton solutions, such as, various combinations of trigonometric periodic function and rational function solutions, various combination of hyperbolic function and rational function solutions. The proposed method is direct, concise and effective, and can be used for many other nonlinear evolution equations. GANIT J. Bangladesh Math. Soc. Vol. 33 (2013) 83-92 DOI: http://dx.doi.org/10.3329/ganit.v33i0.17662